2015
DOI: 10.1063/1.4913451
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surface damage region and edge recombination on the effective lifetime of silicon wafers at low illumination conditions

Abstract: Extremely low surface recombination velocities on crystalline silicon wafers realized by catalytic chemical vapor deposited SiN x / a-Si stacked passivation layers Appl. Phys. Lett. 97, 082108 (2010); 10.1063/1.3483853 Effect of surface passivation on generation and recombination lifetimes in silicon wafer studied by impedance spectroscopy Appl. Phys. Lett. 96, 162109 (2010); 10.1063/1.3385779 Spatially resolved modeling of the combined effect of dislocations and grain boundaries on minority carrier lifetime i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…Recent reports have found that higher temperature oxidation annihilates in‐grown defects in FZ silicon, providing a stable and higher quality benchmark for surface passivation studies . For the a‐Si and AlO x structures, this can be explained by the plasma damage occurring during film deposition as has also been reported . It is noted that the highest positive bias applied to the AlO x stacks in Figure b was less than for others in Figure .…”
Section: Carrier‐dependent Surface Recombination In Siliconsupporting
confidence: 51%
“…Recent reports have found that higher temperature oxidation annihilates in‐grown defects in FZ silicon, providing a stable and higher quality benchmark for surface passivation studies . For the a‐Si and AlO x structures, this can be explained by the plasma damage occurring during film deposition as has also been reported . It is noted that the highest positive bias applied to the AlO x stacks in Figure b was less than for others in Figure .…”
Section: Carrier‐dependent Surface Recombination In Siliconsupporting
confidence: 51%
“…We dice specimens after oxidation and thus such size will reduce the maximum effective lifetime well below its intrinsic bulk limit due to edge recombination as reported in refs. [26,27]. For the corona-charged and ion-charged specimens, at low injection conditions, τ eff is maximized as surface SRH recombination is minimized through field effect.…”
Section: Field Effect Passivation From Alkali Ion Charged Siomentioning
confidence: 99%
“…[ 17,18 ] Their presence can be attributed to recombination centres originating from various sources, including: i) deep‐level defects in the silicon bulk, such as the boron–oxygen (B–O) complex, metal impurities, and oxygen precipitate‐related defects; [ 19–21 ] ii) the presence of surface defects or dielectric layers (AlO x and SiN x ) with high fixed charge densities; [ 22–24 ] and iii) edge recombination. [ 22,24,25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 25 ] demonstrated that the presence of edge recombination and localized recombination increases the apparent injection dependence of carrier lifetimes in a manner that appears similar to Shockley–Read–Hall recombination. Hameiri et al [ 22 ] through a comprehensive investigation, elucidated the influence of surface damage regions and edge recombination on the injection dependence in both p‐and n ‐type samples, passivated by dielectric films. Their study suggested that the fixed charge associated with the AlO x and SiN x layers contributes to the strong injection dependence of carrier lifetimes of the samples when a surface damage region and edge recombination is present on the samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation